(3fhQ GdEjVGM hfLGI GdCQhGMs - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf bGd GdYHO CHh GdENdGU MSf GdhaGFj GdTQfHdGdj GdMfaj Cfg GdJeS efj HYV GdCNdG YGedfG Gddg Cf CYed eSGFd GdYHGOGJ eG aUd ef GdeSGFd GdegeGJ aCLHJg hSejJg fhQ GdEjVGM hLGI GdCQhGMs
(3BNQgG (B:s
(3bGd YWG QMeg Gddg JYGdi eKd GdeYJca eKd QLd ONd jJNda Ydi HGH YXje dMGLI aGdeYJca jbRd dG CHQM MJi jZaQ Gddg djs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3eYLe GdeDdajf (B1 / 575s
(3cTa GdXfhf (B2 / 1982s
(3gOjI GdYGQajf (B1 / 292s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs